2012
DOI: 10.1186/2251-6581-11-16
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between serum 25-hydroxy vitamin D concentration and obesity in type 2 diabetic patients and healthy subjects

Abstract: BackgroundBoth obesity and type 2 diabetes are associated with hypovitaminosis D. The aims of this study were to investigate the association of serum 25-hydroxy vitamin D (25(OH) D) and parathyroid hormone (PTH) concentration with body mass index (BMI) in type 2 diabetic patients compared to control subjects and their predicting role in obesity.MethodsThis cross-sectional study was conducted on 200 subjects (100 type 2 diabetics and 100 healthy controls). Concentration of 25(OH) D, calcium, phosphorous, parath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
33
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 39 publications
7
33
1
2
Order By: Relevance
“…In a cross sectional Iranian study by Taheri and colleagues [19], the prevalence of vitamin D deficiency was 83.3% in diabetic patients and 75.6% in healthy subjects. Another cross sectional study among rural and urban adult Indians, Harinarayan et al ., [20] also observed 44% and 62% for rural and urban men respectively and 70% and 75% deficiency for rural and urban women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In a cross sectional Iranian study by Taheri and colleagues [19], the prevalence of vitamin D deficiency was 83.3% in diabetic patients and 75.6% in healthy subjects. Another cross sectional study among rural and urban adult Indians, Harinarayan et al ., [20] also observed 44% and 62% for rural and urban men respectively and 70% and 75% deficiency for rural and urban women respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results are reported in previous studies. [232425] Need et al . [26] showed that the patients who had higher levels of Vitamin D concentration had lower FBS in comparison with the other groups.…”
Section: Discussionmentioning
confidence: 99%
“…[40] Another study carried in Iran showed that prevalence of vitamin D deficiency was higher T2DM patients than controls (82.1% vs.75.6%) but there was no statistical significant difference between both groups as regards to vitamin D level (p=0.75). [41 Also no statistical significant difference between mean level of vitamin D was observed in retrospective study that evaluated the medical records of patients with T2DM and healthy controls in Turkey, 25(OH) vitamin D mean± SD was (21.1±8.6 vs.21.4±11.8) among diabetes patients and controls respectively (p=0.302). [42] However, several studies have demonstrated statistical significant lower vitamin D level among type2 diabetic patient.…”
Section: Discussionmentioning
confidence: 99%